(untitled) (Archives of Clinical Psychiatry, 2014)
Background : Although Alzheimer’s disease (AD) is the most prevalent form of dementia, little is known about cognitive and functional aspects in its advanced stages. Objective : This study aimed the adaptation and correlation among specific instruments for AD in advanced stages with regard to cognition objectively weighted, besides the comparison between static and ecological aspects of functional capacity. Methods : 95 moderate, moderatly severe and severe AD patients (33 men and 62 women) underwent the scales CDR (Clinical for Dementia Rating), FAST (Functional Assessment Scale), MMSE (Mini-Mental State Exame), MMSEsev (Severe Mini-Mental State Examination), SIB-8 (Severe Impairment Battery) and TSI (Test for Severe Impairment), for the comparison with a golden-standard ecological scale the PADL (Performance Activities of Daily Living). Results : The evidence suggests an increasing and statistically significant linear correlation between the ecological functional scale and cognitive tests according to the stratification of AD stages once weighted by static functional scale. Discussion : The results indicate that for patients in advanced stages of AD, appropriate cognitive tests and performance-based functional scales are useful in more accurate assessment of disease staging and monitoring its progression.